2015
DOI: 10.14720/aas.2014.103.2.11
|View full text |Cite
|
Sign up to set email alerts
|

The content of minerals in Slovenian organic and conventional produced fruits, herbs and vegetables

Abstract: The present study aims to compare mineral composition of fruits, herbs and vegetables grown conventionally and according to organic practice. Fruits, herbs and vegetables have been identified as leading dietary source of antioxidants, vitamins and minerals. These compounds are very variable in the composition and in the concentration among cultivars and species. Determination of calcium (Ca), potassium (K), phosphorus (P) sulphur (S) and chlorine (Cl) was performed with Energy dispersive X-ray fluorescence spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Furthermore, our correlation analysis showed that the correlations among K, Mg, Cu, and Mn are different in different forms of cabbage. Several studies have also shown that the correlation between mineral elements varies in cabbage, but no relationship law has been established [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our correlation analysis showed that the correlations among K, Mg, Cu, and Mn are different in different forms of cabbage. Several studies have also shown that the correlation between mineral elements varies in cabbage, but no relationship law has been established [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies indicate certain advantages of organically produced agricultural products, primarily in terms of the impact of the production process on the environment, as well as in terms of quality properties of products [7][8][9]. Some studies, while acknowledging the positive organic production impact on the environment, suggest that there is no significant difference between the organic and the conventional production system in terms of qualitative properties, yield, and morphological agricultural products characteristics of agricultural products [10][11][12][13][14]. Apart from the variety or genotype and the climate and soil conditions, morphological characteristics of the pepper are strongly influenced by the agrotechnical measures applied in the production [1][2].…”
Section: Introductionmentioning
confidence: 99%